PENGARUH TEMPERATUR PADA PROSES TRANSESTERIFIKASI TERHADAP KARAKTERISTIK BIODIESEL DARI MINYAK GORENG BEKAS - Atmoko, Wahyu Puji (Journal of Mechanical Engineering Learning, 2014)
The purpose of this research was to determine the effect of temperature on the quality of the biodiesel transesterification process. Raw materials used in the making process of biodiesel is waste cooking oil. This Research using the transesterification process by react catalyst and methanol then mixed along with the waste cooking oil. The mixing takes one hour each mixing using a variation of temperature of 30Â°C, 40Â°C, 50Â°C and 60Â°C. Then the transesterification proceeds deposited for approximately 24 hours. The results of the precipitation in the form of biodiesel and glycerin is separated. The biodiesel washing process 4 times washing and drying biodiesel by heating with the temperature reaching 112Â°C and cooling. Test results on the density characteristics of temperature variation 30Â°C and 40Â°C of 0.8779 g / ml, 50Â°C for 0.8771 g / ml and a temperature of 60Â°C values ââobtained 0.8747 g / ml. On testing the viscosity temperature 30Â°C, 40Â°C, 50Â°C and 60Â°C resulting value 5.258 mm2 / s, 5.078 mm2 / s, 4.939 mm2 / s, and 4.728 mm2 / s. For the test results to the flash point temperature of 30Â°C is 202.5Â°C, at 40Â°C temperature variation of 198.5Â°C, at temperature 50Â°C obtained 196.5 Â° C and 60Â°C at 192.5Â°C. From the test data, the results obtained characteristic density, viscosity and flash point. The results showed that all of the testing of biodiesel produced meets the standard characteristics of biodiesel. It can be concluded that the use of variations in temperature do not affect the characteristics of the biodiesel. In addition, biodiesel research results according to the criteria of diesel motor fuel.